Cardio-Renal Clinical Challenges - Goldsmith, David; Covic, Adrian; Spaak, Jonas (Springer International Publishing : Imprint: Springer, 2015)
This book provides a comprehensive overview of the clinical challenges faced during the treatment of patients with cardiorenal syndrome (CRS). The bidirectional link that associates renal and cardiovascular diseases means that patients with CRS have an increased risk of hospital admission and mortality as a result of their coexistence yet, there are no agreed guidelines for their management. Cardio-Renal Clinical Challenges takes clinical presentations and clinical problems as its base, and then discusses the evidence for best management of common clinical problems and the reasons for the complex interplay between the cardiac and renal systems. In addition, the link between heart failure and chronic kidney disease (CKD) can impose a considerable epidemiological burden thus this text also aims to address the issue of organizing healthcare to maximize both the opportunities for prevention and best healthcare economic returns. This book will be of immediate value and practical interest to all consulting and trainee cardiologists and renal physicians.